PENGARUH ORGANIZATIONAL LEARNING DAN GREEN HUMAN RESOURCE MANAGEMENT PRACTICES TERHADAP ENVIRONMENTAL PERFORMANCE YANG DIMEDIASI OLEH GREEN COMPETITIVE ADVANTAGE PADA KARYAWAN DI PERUSAHAAN KELAPA SAWIT - simarmata, Immanuel crhyseis edlyn; Febriant, Rizky (Universitas Trisakti, 2025)
This study aims to analyze the influence of organizational learning and green human resource management practices on environmental performance, with green competitive advantage as a mediating variable. A quantitative approach was employed by distributing questionnaires to employees at a palm oil company in South Jakarta. Purposive sampling was applied to select relevant respondents, and data were analyzed using inferential statistical methods. The findings indicate that organizational learning and green human resource management practices positively influence green competitive advantage and environmental performance. Green competitive advantage also mediates the relationship between the independent variables and environmental performance. This study provides practical insights for management in developing sustainability strategies based on learning and human resource development, particularly within the palm oil industry context.